Role of Prokineticin Receptor-1 in Epicardial Progenitor Cells - Canan G. Nebigil; Thu Lan Nguyen; Adelin Gasser (Journal of Developmental Biology, 2013)
G protein-coupled receptors (GPCRs) form a large class of seven transmembrane (TM) domain receptors. The use of endogenous GPCR ligands to activate the stem cell maintenance or to direct cell differentiation would overcome many of the problems currently encountered in the use of stem cells, such as rapid in vitro differentiation and expansion or rejection in clinical applications. This review focuses on the definition of a new GPCR signaling pathway activated by peptide hormones, called “prokineticins”, in epicardium-derived cells (EPDCs). Signaling via prokineticin-2 and its receptor, PKR1, is required for cardiomyocyte survival during hypoxic stress. The binding of prokineticin-2 to PKR1 induces proliferation, migration and angiogenesis in endothelial cells. The expression of prokineticin and PKR1 increases during cardiac remodeling after myocardial infarction. Gain of function of PKR1 in the adult mouse heart revealed that cardiomyocyte-PKR1 signaling activates EPDCs in a paracrine fashion, thereby promoting de novo vasculogenesis. Transient PKR1 gene therapy after myocardial infarction in mice decreases mortality and improves heart function by promoting neovascularization, protecting cardiomyocytes and mobilizing WT1+ cells. Furthermore, PKR1 signaling promotes adult EPDC proliferation and differentiation to adopt endothelial and smooth muscle cell fate, for the induction of de novo vasculogenesis. PKR1 is expressed in the proepicardium and epicardial cells derived from mice kidneys. Loss of PKR1 causes deficits in EPDCs in the neonatal mice hearts and kidneys and impairs vascularization and heart and kidney function. Taken together, these data indicate a novel role for PKR1 in heart-kidney complex via EPDCs.